A one-step fluorescent biosensing strategy for highly sensitive detection of HIV-related DNA based on strand displacement amplification and DNAzymes. Issue 55 (12th September 2018) - Yan, Xiaoyu; Tang, Min; Yang, Jianru; Diao, Wei; Ma, Hongmin; Cheng, Wenbin; Que, Haiying; Wang, Tong; Yan, Yurong
Abstract : A one-step fluorescent biosensing strategy for highly sensitive detection of HIV-related DNA based on strand displacement amplification and Mg 2+ -dependent DNAzyme reaction. Abstract : Sensitive and specific detection of HIV-related DNA is of great importance for early accurate diagnosis and therapy of HIV-infected patients. Here, we developed a one-step and rapid fluorescence strategy for HIV-related DNA detection based on strand displacement amplification and a Mg 2+ -dependent DNAzyme reaction. In the presence of target HIV DNA, it can hybridize with template DNA and activate strand displacement amplification to generate numerous DNAzyme sequences. With the introduction of Mg 2+, DNAzyme can be activated to circularly cleave the substrate DNA, which leads to the separation of fluorophore reporters from the quenchers, resulting in the recovery of the fluorescence. Under the optimal experimental conditions, the established biosensing method can detect target DNA down to 61 fM with a linear range from 100 fM to 1 nM, and discriminate target DNA from mismatched DNA perfectly. In addition, the developed biosensing strategy was successfully applied to assay target DNA spiked into human serum samples. With the advantages of fast, easy operation and high-performance, this biosensing strategy might be an alternative tool for clinical diagnosis of HIV infection.